If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -5h = 9z + 7 Reorder the terms: 12 + -5h = 7 + 9z Solving 12 + -5h = 7 + 9z Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -5h = 7 + -12 + 9z Combine like terms: 12 + -12 = 0 0 + -5h = 7 + -12 + 9z -5h = 7 + -12 + 9z Combine like terms: 7 + -12 = -5 -5h = -5 + 9z Divide each side by '-5'. h = 1 + -1.8z Simplifying h = 1 + -1.8z
| 5x-9=-44 | | -9+10h=8h-5h-2 | | (6x-10)=(6x+10) | | x+3x-56=2x | | 19p^2+2p+8=x | | -9-5w=-6w | | 6x-10=6x+10 | | -6-n=8+n-4 | | 6x^2+3x-1=0 | | -12+5t^2-4t= | | 4x+4=4x+4 | | 7n-1=-10+8n | | 100*12-(6)+12/4= | | 9b^2-60b-21= | | 42.3=1.5d+3.2s | | 6v^2-7v+1= | | 12(x+3)+7(6x-3)=x+13(4x-3)+57 | | 4c+10c^2-14= | | 49=10p-9p | | 5x+3=2(x+2) | | 7x^2-3x-2=0 | | -16-2x=7x+22 | | 10b^2-8b-24= | | 4m+2=18 | | 13d+6=5d+46 | | 3n-1=-19 | | -6w+2=2+5w | | 11-5z=26 | | (x-17)(x-17)=8 | | 4v=10+5v | | -7g=5-6g | | 172-3x=24x+16 |